2020
DOI: 10.1007/s40843-019-1272-0
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the deep-tissue photothermal therapy in near-infrared II region based on tumor-targeted MoO2 nanoaggregates

Abstract: Research on deep-tissue photothermal therapy (PTT) in the near-infrared II (NIR-II, 1000-1350 nm) region has bloomed in recent years, owing to higher maximum permissible exposure and deeper tissue penetration over that in the near-infrared I (NIR-I, 650-950 nm) region. However, more details need to be uncovered to facilitate a fundamental understanding of NIR-II PTT. Herein, a tumor-targeted therapeutic nanosystem based on NIR-responsive molybdenum oxide (MoO 2) nanoaggregates was fabricated. The photothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…S23) of mice treated with different groups (PBS and MoO 3−x @PPSNs) after laser irradiation showed that no evident damage was observed at the tumor site of the mouse treated with PBS plus NIR irradiation, while apparent eschar appeared at the tumor region of the mouse treated with MoO 3−x @PPSNs plus NIR irradiation. This can be attributed to the high temperature-induced damage of the tumor and skin tissues, which is consistent with the previous reports [50][51][52]. In addition, all animals survived during the whole treatment process (Fig.…”
Section: In Vivo Anti-tumor Efficacysupporting
confidence: 92%
“…S23) of mice treated with different groups (PBS and MoO 3−x @PPSNs) after laser irradiation showed that no evident damage was observed at the tumor site of the mouse treated with PBS plus NIR irradiation, while apparent eschar appeared at the tumor region of the mouse treated with MoO 3−x @PPSNs plus NIR irradiation. This can be attributed to the high temperature-induced damage of the tumor and skin tissues, which is consistent with the previous reports [50][51][52]. In addition, all animals survived during the whole treatment process (Fig.…”
Section: In Vivo Anti-tumor Efficacysupporting
confidence: 92%
“…Metal sulfide and oxide materials have attracted wide attention because of their special properties such as free electron transfer characteristics, magnetism ( Gao et al, 2017 ), structure, and photothermal stability ( Dahoumane et al, 2016 ; Ge et al, 2016 ; Vena et al, 2016 ; Guo et al, 2020 ). The unique vacancy structure of copper sulfide, and the LSPR caused by the conduction electron resonance oscillation provide possibility for the study of PTT in NIR-II.…”
Section: Nir-ii Absorbing Materialsmentioning
confidence: 99%
“… Liu et al (2020b) synthesized chitosan (CS) coated RuO 2 NPs (CS-RuO 2 NPs) with a one-pot method, which has unique potential in low-temperature PTT. Guo et al (2020) synthesized MoO 2 nano-aggregates by hydrothermal synthesis. It has strong cell penetration at 1,064 nm.…”
Section: Nir-ii Absorbing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tri-therapeutic strategies have successfully eliminated tumors both in vitro and in vivo (Curcio et al, 2019 ). Similarly, other MNPs, including Mo, Pd, Pt, Mn, and Bi nanoparticles, have been extensively investigated as excellent phototherapy and imaging agents, which can be used in clinical studies based on their biocompatible behaviors (Badrigilan et al, 2020 ; Guo et al, 2020b ; Jiang et al, 2020 ; Qian et al, 2020 ).…”
Section: Application Of Stimuli-triggered Metallic Nanotherapeutics Imentioning
confidence: 99%